Implementation of the ‘active customer’ concept in the EU and Ukraine law - Shvorak, O. M. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article explores the evolution of the concept of the “active consumer” (prosumer) in the energy law of the European Union and Ukraine. It examines the prerequisites for the emergence of this notion in the 2000s, driven by technological advances in photovoltaic solar panels, the declining costs of equipment, and the introduction of national support schemes for green energy. Initially absent from legal frameworks, the concept of the prosumer gradually gained attention in both academic and policy debates. A milestone in its development was the adoption of the Framework Strategy for a Resilient Energy Union with a Forward-Looking Climate Change Policy (2015), which recognized consumers as active participants in energy markets. This approach was reinforced by the Clean Energy for All Europeans package (2016), which established institutional foundations for self-generation, energy communities, and non-discriminatory participation of households in electricity markets. The formal legal recognition of prosumers was achieved through Directive (EU) 2018/2001 (RED II) and Directive (EU) 2019/944 (IEMD). RED II introduced the categories of renewables self-consumers and renewable energy communities, while IEMD provided additional guarantees for active consumers’ participation in retail and wholesale markets, emphasizing non-discrimination and consumer protection. However, the practical implementation in EU Member States has shown uneven progress, with significant delays and gaps that hinder the development of decentralized generation. Ukraine, having undertaken commitments under the Energy Community, integrated a range of RED II and IEMD provisions into national law, particularly through amendments to the Law of Ukraine “On the Electricity Market.” The legislation introduced the net billing mechanism and defined the legal status of active consumers, specifying conditions for households and non-household users. Despite notable progress, economic incentives and tariff limitations remain a challenge, reducing households’ interest in investing in small-scale generation. The article concludes that to fully unlock the potential of active consumers, Ukraine must enhance financial incentives, broaden access to flexible market mechanisms, and accelerate the implementation of smart grid technologies.